The Thermal Stability of Janus Monolayers SnXY (X, Y = O, S, Se): Ab-Initio Molecular Dynamics and Beyond - Yufeng Luo; Shihao Han; Rui Hu; Hongmei Yuan; Wenyan Jiao; Huijun Liu (Nanomaterials, 2021)
In recent years, the Janus monolayers have attracted tremendous attention due to their unique asymmetric structures and intriguing physical properties. However, the thermal stability of such two-dimensional systems is less known. Using the Janus monolayers SnXY (X, Y = O, S, Se) as a prototypical class of examples, we investigate their structure evolutions by performing ab-initio molecular dynamics (AIMD) simulations at a series of temperatures. It is found that the system with higher thermal stability exhibits a smaller difference in the bond length of Sn–X and Sn–Y, which is consistent with the orders obtained by comparing their electron localization functions (ELFs) and atomic displacement parameters (ADPs). In principle, the different thermal stability of these Janus structures is governed by their distinct anharmonicity. On top of these results, we propose a simple rule to quickly predict the maximum temperature up to which the Janus monolayer can stably exist, where the only input is the ADP calculated by the second-order interatomic force constants rather than time-consuming AIMD simulations at various temperatures. Furthermore, our rule can be generalized to predict the thermal stability of other Janus monolayers and similar structures.